PERAN ORANG TUA DALAM MENYIKAPI GADGET DAN IMPLIKASINYA TERHADAP PENYIMPANGAN PERILAKU SEKSUAL ANAK - Lilik Supriyono (Universitas Muhammadiyah Surakarta, 2020)
The purpose of this study is to describe the role of parents in responding to gadgets and their implications for deviant sexual behavior in children. The method used by researchers in compiling this research is a descriptive qualitative method. Data were collected through observation, interviews, and documentation. The results of this study are as follows: The frequency of gadget use needs to be limited. Children do not need to be given excessive gadgets, because the most important thing is that children can use them and know their optimal uses. The intensity of excessive use of gadgets can lead to sexual deviations in children. The role of parents in addressing the use of gadgets to their children is very important. This is done so that children do not abuse their parents’ trust in them. The attitude that needs to be shown is accompanying children when playing gadgets and parents must be able to operate it. As for the impact that may arise if parents do not supervise the use of gadgets on their children, then their children will carry out deviant behavior. The form of the deviation is in the form of bad attitude and speech. Usually in the form of an erotic attitude and obscene speech.